Teaching and Learning Approaches: Curriculum Framework for Sustainability Literacy for Technical and Vocational Teacher Training Programmes in Malaysia - Caleb Chidozie Chinedu, Caleb Chidozie Chinedu; Saleem, Atif; Wan Muda, Wan Hanim Nadrah (Mdpi, 2023)
Given the impact of unsustainable practices, work, and living patterns, it has become increasingly important to raise global citizens as stewards of the earth’s life support system. Thus, developing sustainability literacy has become very crucial. A sustainability-literate professional can make sound decisions and act in environmentally friendly, socially acceptable, and economically viable ways. Technical and vocational education and training (TVET) arguably has the potential to educate workers, graduates, and citizens alike in developing sustainability literacy since it is regarded in many nations as the supplier of skilled labour. TVET teacher training programmes in Malaysia have been vastly proficient in developing vocationally competent teachers and workers. Still, there remains uncertainty regarding the extent to which these vocational teaching professionals have been trained to develop sustainability competencies and literacies. The implication is that, when technical and vocational teachers responsible for training workers do not possess the requisite competencies to engage in sustainability education, the potential for TVET to become a viable tool for ESD diminishes. Given this backdrop, this study was undertaken to propose a curriculum framework for sustainability literacy for technical and vocational teacher training programmes. Using a modified Delphi method (MDM) consisting of 15 expert participants from Asian-Pacific countries, four important curricular elements for sustainability literacy were identified and defined. These include the learning outcomes for sustainability literacy, teaching competencies for sustainability literacy, pedagogical approaches to foster effective teaching and learning for sustainability, as well as ESD integration strategies. The specific indicators within this curriculum framework were also defined. The paper concludes with vivid implications for practice within TVET teacher training programmes in realising Goal 4 of the United Nations Sustainable Development Goals (SDGs).